Compositional model of the website as a dominant genre - Topolnicka, Elwira (Papers in Linguistics, 2019)
The purpose of the article is to present the website as an independent genre presenting a coherent vision of the world of the sender or senders, whose intention is implemented in a specific compositional model. Referring to the concept of Maria Wojtak, the structural aspect of the species pattern was developed. Recognizing the website as a genre in the form of a collection, the delimitation frame, compositional dominant, relative autonomy of components and structural finalization have been analysed. The article reviews the polysemiotic texture of the website and its strategic structural components have been distinguished. The triple-facetted website design has been distinguished in the form of the initial part (headline), the main part (content) and the final part (footer). In addition, three models of website structure implementation have been identified, i.e. a one-page, multi-page and a hybrid structure.